Expression of tryptophan 2,3-dioxygenase in mature granule cells of the adult mouse dentate gyrus - Ohira, Koji (BioMed Central, 2010)
New granule cells are continuously generated in the dentate gyrus of the adult hippocampus. During granule cell maturation, the mechanisms that differentiate new cells not only describe the degree of cell differentiation, but also crucially regulate the progression of cell differentiation. Here, we describe a gene, tryptophan 2,3-dioxygenase (TDO), whose expression distinguishes stem cells from more differentiated cells among the granule cells of the adult mouse dentate gyrus. The use of markers for proliferation, neural progenitors, and immature and mature granule cells indicated that TDO was expressed in mature cells and in some immature cells. In mice heterozygous for the alpha-isoform of calcium/calmodulin-dependent protein kinase II, in which dentate gyrus granule cells fail to mature normally, TDO immunoreactivity was substantially downregulated in the dentate gyrus granule cells. Moreover, a 5-bromo-2'-deoxyuridine labeling experiment revealed that new neurons began to express TDO between 2 and 4 wk after the neurons were generated, when the axons and dendrites of the granule cells developed and synaptogenesis occurred. These findings indicate that TDO might be required at a late-stage of granule cell development, such as during axonal and dendritic growth, synaptogenesis and its maturation.